Insect acoustic communication: The role of transmission channel and the sensory system and brain of receivers. (25th March 2019) - Römer, Heiner
Abstract: For decades, acoustic insects have been used as model organisms for behavioural neurobiologists to understand mate choice or predator avoidance, because behaviour can easily and reliably be elicited in the laboratory, and behaviourally relevant, identified nerve cells be studied under these conditions. However, signalling often takes place in complex environments, in which the signal perceived by the receiver may differ greatly from the one broadcast due to the biotic and abiotic properties of the sound transmission channel. Thus, the key challenge is to transfer the insights of these laboratory‐oriented experiments to more natural settings. Signal detection, identification and discrimination, as well as localization, are complicated by the transmission channel in several ways. Here, I review the empirical evidence from outdoor studies, demonstrating how excess attenuation reduces the active space and the information of a signal at some distance from the sender. At the same time, these frequency‐dependent processes allow to maintain acoustic distances to neighbours in a population. Insects often communicate within choruses of signallers of the same and different species, giving rise to high levels of acoustic masking interference. I discuss the evidence found for temporal or spatial partitioning of species in multispecies assemblages, and I show that solutions to the masking problem are based on a combination of adaptations in the behaviour of signallers and in the sensory system of receivers. Whether or not the perceived signal elicits a behaviour in receivers will depend on the design of the sensory system and the brain. I give examples for active mechanical processes in insect sensory receptors that influence the responses to external stimuli. In addition, neuronal filters in the frequency, intensity or time domain, and even the memory of individual receivers, provide the basis for adaptive receiver decision‐making in mate choice scenarios. Finally, I describe the advantages of having access to the relatively simple nervous systems of insects and how this access, combined with the use of a variety of behavioural tests, allows new insights into acoustic communication and its evolution. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.